2015
DOI: 10.1371/journal.pone.0126249
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin Restores Endothelium-Dependent Relaxation in Rat Aorta Rings Impaired by High Glucose: A Novel Insight into the PPARβ-NO Signaling Pathway

Abstract: Polydatin, a natural component from Polygonum Cuspidatum, has important therapeutic effects on metabolic syndrome. A novel therapeutic strategy using polydatin to improve vascular function has recently been proposed to treat diabetes-related cardiovascular complications. However, the biological role and molecular basis of polydatin’s action on vascular endothelial cells (VECs)-mediated vasodilatation under diabetes-related hyperglycemia condition remain elusive. The present study aimed to assess the contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…Importantly, some of these effects result from a direct effect of HG on the vasculature. For example, Wu et al demonstrated that 55 mM HG directly impaired vasorelaxation [36]. Consistent with these earlier reports, we also found that aortas incubated with 30 mM HG, a concentration which mimics glucose levels more closely to that found in diabetic patients with poor glucose control, also displayed impaired endotheliumdependent vasorelaxation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, some of these effects result from a direct effect of HG on the vasculature. For example, Wu et al demonstrated that 55 mM HG directly impaired vasorelaxation [36]. Consistent with these earlier reports, we also found that aortas incubated with 30 mM HG, a concentration which mimics glucose levels more closely to that found in diabetic patients with poor glucose control, also displayed impaired endotheliumdependent vasorelaxation.…”
Section: Discussionsupporting
confidence: 92%
“…These findings provide novel insight into the antioxidant effects of EA in blood vessels under diabetic conditions. Exposure of vascular cells and blood vessels to glucose concentrations ranging from 4.2 g/L (23.1 mM) to 10 g/L (55 mM) for 24 hours resembles the diabetic milieu within cell culture systems [36,[68][69][70][71] and closely mimics a hyperglycemic environment in the vasculature of individuals with diabetes. Several studies have shown that endothelial dysfunction arises even after short-term hyperglycemic injury is inflicted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from the thoracic aorta samples using TRIzol solution (Thermo Fisher Scientific, Inc., Waltham, MA, USA), quantified by ultraviolet spectrometric detection using BioPhotometer Plus (Eppendorf, Hamburg, Germany) according to the manufacturer's protocol (24) and reverse transcribed into complementary DNA using a PrimeScript RT Reagent kit (Takara Biotechnology, Co., Ltd., Dalian, China), according to the manufacturer's protocol. qPCR analysis was performed to analyze the mRNA expression of eNOS, iNOS and nNOS using the SYBR Premix Ex Taq II kit (Takara Biotechnology, Co., Ltd.) with a program of 30 sec at 95˚C, followed by 40 cycles of 15 sec at 95˚C and 1 min at 60˚C.…”
Section: Rna Extraction and Reverse Transcriptase-polymerase Chain Rementioning
confidence: 99%
“…According to the method for NOS activity established by Wu et al (24), the total (t)NOS [constitutive (c)NOS and iNOS] and iNOS activities were assayed in accordance with the NOS typed assay kit (cat. no.…”
Section: Determination Of Nos Activity and No Contentmentioning
confidence: 99%